Controverses autour d’une liaison. Géographie du potentiel conflictuel à travers le projet d’équipement du Danay (La Clusaz — Le Grand Bornand) - Amandine Troiano; Lionel Laslaz (Revue de Géographie Alpine)
This article proposes to analyze an old project, which is not necessarily an active controversy but which was put back in the center of the debates by the SCoT Fier-Aravis in 2019. This project is the connection between the areas of ski resorts of La Clusaz and Le Grand Bornand by the Danay mountain, in the Aravis massif. This sector, which is currently not equipped, would make it possible to create a vast linked domain, capable of competing in part with others in the Northern Alps. But this project, in addition to the questions about the intermittence of the discussions concerning it and its feasibility, raises environmental challenges in a massif considered as little equipped until now. It is therefore interesting to question the notion of conflict potential—the basis of which this article proposes to establish—and the risks of environmental conflict arising if the link were to become more formalized. In addition to the heuristic value of the notion, the article allows us to question in a distanced way the forms of “headlong rush” denounced by the opponents of this type of extension, because other equipment projects may result from it. This same opposition is indicative of a process of territorialization, making the consultation phase of an urban planning document such as the SCoT a time for analyzing conflictual dynamics and potentially for the evolution of local governance. The potential for conflict is then expressed through the capacity for mobilization that this type of project can catalyze against it, structuring collectives that were previously dispersed and poorly federated.